Medical Records System with Blockchain (Health Chain) - Sia, Xing Yan; Abdollah, Aziah; Abdul Majid, Nur Amira; Razali, Md Saifullah (Journal of Advanced Research Design, 2024)
This study explores the potential of blockchain technology to address key challenges in Malaysia’s healthcare system, such as fragmented data, security vulnerabilities and restricted patient data access rights. This paper presents Health Chain, a blockchain-enabled, patient-centric medical record system designed to overcome these significant issues. Health Chain enhances security for patient data by up to 63.2% compared to similar systems, leveraging the immutability and decentralization inherent in blockchain technology. The system employs cryptographic hashing and encryption methods to create a secure architecture and it empowers patients with greater control over their data through smart contracts. Comprehensive evaluation, including User Acceptance Testing (UAT), questionnaires and system testing, revealed promising results: users expressed 17% higher confidence in data security compared to other systems, with 85% finding data management tasks intuitive and easy. Health Chain also optimized administrative procedures, reducing manual data entry time, thereby enhancing healthcare efficiency and potentially leading to cost savings. These findings suggest that Health Chain could revolutionize the healthcare industry by prioritizing data security, empowering users and streamlining processes. Aligned with the vision of SDG 3, which promotes good health and well-being, Health Chain demonstrates significant potential in improving data security, enhancing patient control and reducing administrative burdens. However, further development is needed to address limitations in the scope of services provided. By overcoming these challenges and fostering continuous research and collaboration, Health Chain could play a crucial role in empowering patients, optimizing healthcare efficiency and contributing to a healthier future for all.